SOME ASPECTS OF THE STUDENTS' READINESS TO ACTIVITY IN AN ENVIRONMENT OF INSTITUTIONAL REPOSITORY (Journal of Information Technologies in Education (ITE), 2014)
The article investigated the state of development of specific digital libraries – institutional repositories. In the article described the features of their use in scientific research work of the students. This research contains an interview. It identified the major trends of use e-information in the studying and scientific work.
Keywords: digital library; institutional repositories; open access; self-archiving